Feeding ecomorphologies in the fish genus Herichthys (Perciformes: Cichlidae) based on stomach content and lower pharyngeal jaw shape - Pérez-Miranda, Fabian; Mejía, Omar; Zúñiga, Gerardo; Soto-Galera, Eduardo; Rican, Oldrich (Revista de Biología Tropical, 2019)
Speciation is a multifactorial process with factors acting at different scales of space and time. Trophic niche segregation has promoted the diversification of cichlids fishes in lentic (lacustrine) environments, whether this is also the case in lotic (riverine) systems remains unknown. Herichthys is the genus of cichlids with the most boreal distribution in the Americas comprising 12 currently recognized species, most micro-endemic and only two with a wide distribution. In the present work, we analyzed the stomach content and lower pharyngeal jaw morphologies of the species of the genus to evaluate the possible role of feeding ecology in the diversification of the group. Trophic strategies varied widely, including omnivores, piscivores, invertivores, molluskivores, detritivores, herbivores and algivores. Low values of Pianka’s index of niche overlap were found in the sympatric micro-endemic species, while in the widely distributed species the indices ranged from low to very high. The analysis of lower pharyngeal jaw morphologies allowed discriminating a shape associated with piscivorous species from other foraging groups. The results of this study suggest that trophic niche segregation is a factor that could promotes diversification within the genus Herichthys although additional studies need to be performed to fully understand the speciation process in this group of Neotropical cichlid fishes.